2017
DOI: 10.5935/abc.20170068
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Economic Impact of Cardiovascular Diseases in the Last Five Years in Brazil

Abstract: BackgroundThere is growing concern about the economic impact of cardiovascular diseases (CVD) in Brazil and worldwide.ObjectiveTo estimate the economic impact of CVD in Brazil in the last five years.MethodsThe information to estimate CVD costs was taken from national databases, adding the direct costs with hospitalizations, outpatient visits and benefits granted by social security. Indirect costs were added to the calculation, such as loss of income caused by CVD morbidity or mortality.ResultsCVD mortality acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0
36

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(81 citation statements)
references
References 7 publications
1
44
0
36
Order By: Relevance
“…There is scarce evidence on the economic impact of cardiovascular diseases and low‐and medium‐income countries, although studies are increasingly being published in Brazil and in Latin America . Recent studies have shown that CVDs are the main cause of years lost to premature death and have a large economic impact on society (estimated at 9.5% of the Gross National Product), considering direct health costs and indirect costs, such as premature retirements and productivity losses …”
Section: Introductionmentioning
confidence: 99%
“…There is scarce evidence on the economic impact of cardiovascular diseases and low‐and medium‐income countries, although studies are increasingly being published in Brazil and in Latin America . Recent studies have shown that CVDs are the main cause of years lost to premature death and have a large economic impact on society (estimated at 9.5% of the Gross National Product), considering direct health costs and indirect costs, such as premature retirements and productivity losses …”
Section: Introductionmentioning
confidence: 99%
“…In 2016, Cardiovascular Diseases (CVD), particularly heart diseases, had the highest mortality rates and Disability-Adjusted Life Years (DALYs) in both genders in Brazil 5 . Also worth noting are the high costs of hospitalizations and treatment in Brazil's Public Health System (Sistema Único de Saúde -SUS), as well as the indirect costs caused by reduced productivity, time off work, and the negative effects on the quality of life of sick individuals and their family members 6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…O impacto socioeconômico das doenças crônicas está aumentando e é considerado um problema para a saúde pública mundial. Além das mortes prematuras, as DCNT são responsáveis pela incapacidade para o trabalho, pela redução dos rendimentos familiares e pela redução da produtividade (SIQUEIRA, FILHO, LAND, 2017).…”
Section: Introductionunclassified